Development of novel correlative light and electron microscopy linkage system using silicon nitride film. (4th January 2019) - Haruta, Tomohiro; Ikeda, Yuta; Konyuba, Yuji; Fukuda, Tomohisa; Nishioka, Hideo
Abstract : In this paper, we investigated the optical characteristics of SiN film, and revealed that thin SiN film shows high light transmittance and low autofluorescence. Subsequently, we developed novel CLEM linkage system with SiN film, and succeeded in CLEM observation of blue toner using this CLEM linkage system. Abstract: In this study, we investigated the optical properties of a silicon nitride (SiN) film. The thin SiN film (30 nm thick) exhibited good light transmittance and little autofluorescence and could be used as a microscope slide for optical microscopy (OM). In addition, we developed a novel correlative light and electron microscopy (CLEM) that combines OM with transmission electron microscopy (TEM) using an SiN thin film. In this system, CLEM was performed by replacing a detachable retainer with a holder for TEM and an adaptor for OM. The advantage of this method is that the same specimens can be sequentially observed using suitable OM and TEM.